Headgear Design for Protecting the Eyes of Jaundiced Newborn During Phototherapy Treatment - Nasom, Chananchida; Chonsakorn, Sakorn; Srivorradatpaisan, Supanicha (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2023)
This study focused on two main aims: 1) to evaluate a suitable fabric for newborns; and 2) to study a headgear design for eyes protection in newborns, both premature and mature. The research method consisted of 2 steps: 1) to study 5 types of fabrics including 100 % cotton salou fabric, 100 % cartoon pattern salou fabric, 100 % polyester fiber lint, 100 % polyester fiber chicken skin fabric and 100 % polyester nano. The physical test found the abrasion test of 100 % cotton fabric with cartoon pattern salu had a rubbing fastness at level 4 out of 5 levels. A test for color fastness of washing and pressing with heat showed that there was color variation at level 4/5 and the color staining on white cloth was level 4/5. A test of color fastness to heat pressing showed that both the degree of color change and the staining on white fabric were at level 4/5. to the second step (2) was to study 5 styles of headgear including sewn-on film type, open-close type, chin strap type foldable hat style and open forehead. The research instrument was a questionnaire of satisfaction (IOC) with a reliability coefficient of 0.60. The result showed that 100 % cotton cartoon salou fabric was suitable and feasible for newborns, with an average rating of 4.26. The outstanding properties were well-ventilated and transparent, easy to clean, heat resistant to light, safety for baby's skin, and non-irritating. There were cute, modern fabric patterns suitable for newborns and the baby bonnet design had a high-level satisfaction, with an average rating of 4.42. From the test results, it can be concluded the fabric is convenient to use and beneficial to medical textile products.